Musculoskeletal physiotherapists' perceptions of non-responsiveness to treatment for cervicogenic headache. (2013) - Liebert, Ann; Rebbeck, Trudy; Elias, Sandra; Hawkins, David; Adams, Roger
Abstract : Cervicogenic headache (CH) is a debilitating pain problem, estimated to affect 13–17% of the population with chronic headache. Physiotherapy can improve this condition in 75% of patients but the remaining 25% are unresponsive to treatment, and to date researchers have been unable to identify predictors of non-responsiveness. The aim of this study was to seek both consensus and alternative accounts by examining the perceptions of experienced musculoskeletal physiotherapists regarding the features associated with non-responsiveness to treatment in adults and children with CH. A cross-sectional study was conducted (response rate 74%) in which 90 physiotherapists were asked about factors influencing non-responsiveness, using both written responses and Visual Analog Scale ratings, ranging from 0 (strongly disagree) to100 (strongly agree). The means for features in adult CH that physiotherapists rated as being most related to non-responsiveness were: history of severe trauma, 60 SD 27; genetic history of CH or other headache types, 55 SD 24; neural sensitivity, 49 SD 21; minimal presence of upper cervical neck pain and impairment, 55 SD 26; immunological comorbidities, 51 SD 26; and latency of response to treatment, 50 SD 26. These same features were considered to be associated with CH in children, but without the non-responsiveness of adults.